Educação geográfica inclusiva: concepção de professores sobre aprendizagem de estudantes cegos em João Pessoa - Santos, Irecer Portela Figueirêdo (2023)
In this research we present an analysis of the perception that Geography teachers have about their inclusive pedagogical practices and their reflections on the learning of blind students in the municipality of João Pessoa, in the State of Paraíba. Some questions were raised and guided this research, namely: is the presence of blind students frequent in regular classrooms? Are there difficulties for teachers in conducting the learning of blind students? How do teachers feel when the blind student arrives in the classroom? How did you develop pedagogical activities in geographic education? Participants were 35 Geography teachers, 5 blind students and 1 Administrative Director of the Institute for the Blind of Paraíba Adalgisa Cunha. The time frame for the analysis of the experiences that the teachers had was from 2015 to 2019. The theoretical framework was based on authors who discuss inclusion and educational policies, such as Mantoan (2002, 2006, 2013) and Sassaki (2005); geographic education (Castellar, 2005, 2019; Cavalcante, 2013) and mediation of learning (Vigotsky, 1984; Feuerstein, 2014), especially for visually impaired and blind people. We also used educational documents, statistical data available at the Anísio Teixeira National Institute of Educational Studies and Research, and microdata from the School Census of Basic Education (MEC/INEP). We opted for qualitative research, complemented with quantitative data. Different instruments were used for data collection. Thus, the study was divided into three stages, with the use of different instruments and strategies appropriate to each one. First, we applied a questionnaire via the Google Forms platform, in which 31 teachers participated randomly, to survey how often blind students are enrolled in regular schools. Second, we interviewed, in a semi-structured way, four teachers who declared that they had worked with blind students, and 5 five blind students. And third, we sent a questionnaire via e-mail to be answered by a representative of the Institute for the Blind of Paraíba Adalgisa Cunha. To process the data, we use categories from content analysis, grouping them by similar data. The results perceived during the analysis are that there is a seasonality in the frequency of enrollment of blind students in the regular school system, and this reflects in the lack of experience and clarity of Geography teachers in conducting learning for the spatial reasoning of these students. The most efficient pedagogical practices were not evident so that they could be presented here. This indicates that more important than wanting to include blind students, is for the teacher to be inclusive, because in this way, both are built as learners and constitute themselves as full citizens.